Mind the "Attitude-behaviour Gap" in the Ethical and Sustainable Decision Making: An Application of Neutralization Theory - Gao, Mingyang (2013)
It is believe that there is an “attitude-behaviour gap” in the ethical and sustainable decision making (e.g. Carrigan et al, 2004). Some individuals claim they have relatively high levels of positive attitudes towards certain ethical and sustainable behaviour. However, their positive attitudes may not fully translate into their actual behaviours. In order to explain, predict and change this discrepancy, social psychological behaviour change models such as the Theory of Planned Behaviour (TPB, Ajzen, 1985, 1987) is adopted as the basic framework to examine certain specific behaviour. In addition, neutralization theory (Sykes and Matza, 1957) is used in this research to explain the reason why individuals behave less ethically and sustainably despite their positive attitudes and beliefs. The research model of Chatzidakis et al (2007) is adopted to a novel ethical and sustainable context, the usage of non-reusable plastic bag in grocery shopping in China. This research is quantitative based research. Quantitative research method, namely questionnaire, examines the relationships of the psychological factors of behavioural intention. In addition, qualitative research method is used in elicitation questionnaire and open questions in main questionnaire, which generates in-depth insights for quantitative research. The findings of this research could be helpful to make governmental regulations and social marketing massages.